Measuring the New Construct 'Ethics and Norms-Based Work': A Construction from Human Capital Theory with Religious Norms in Indonesia - Hasmin, Hasmin; Nurung, Jumiaty (Paradoks : Jurnal Ilmu Ekonomi, 2025)
Purpose: This study aims to develop the "Ethics and Norms-Based Work" (ENBW) construct by integrating Human Capital Theory with ethical and religious norms within the Indonesian context, addressing significant gaps in the existing literature. Methodology/Approach: The research employed a holistic approach, utilizing Structural Equation Modeling (SEM) with Amos to analyze data collected from 137 professionals across diverse sectors, including civil servants, educators, entrepreneurs, and employees of state-owned enterprises in South and West Sulawesi. Findings: The findings underscore the importance of incorporating ethical and moral values into human capital development. This integration not only enriches the understanding of human capital but also promotes a more ethical, productive, and inclusive work environment. Additionally, it supports economic, social, and environmental sustainability. Theoretical and Managerial Implications: For academics, the ENBW construct offers a new perspective on Human Capital Theory, emphasizing the integration of ethical principles into human resource development strategies. For practitioners, the findings provide actionable insights for fostering ethical behavior and sustainability within organizations. Research Limitations: The study is limited to a specific geographic region within Indonesia and a sample size of 137 professionals, which may affect the generalizability of the findings. Future research should consider broader geographic and sectoral scopes to validate and extend the applicability of the ENBW construct.